Methane reforming over a high temperature stable-NiCoMgOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Chemical Engineering Journal, 2006)
The unusually high temperature stable NiCoMgOx (Ni/Co/Mg: 1:0.2:1.2)/zirconia-hafnia catalyst has been investigated for syngas generation via the catalytic partial oxidation of methane (CPOM), oxidative steam reforming of methane (OSRM) and oxidative CO2 reforming of methane (OCRM) processes. The catalyst, even when calcined at 1400 degrees C for 4 h, showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions. On account of its high thermal stability, hot spots in the catalyst bed and/or high temperatures prevailing at the catalyst surface during the oxy-reforming processes would have little or no effect on the catalytic activity/selectivity of the NiCoMgOx/zirconia-hafnia catalyst, thus making the catalyst suitable even for operating under adiabatic conditions. While the selectivity for CO increased considerably with increasing reaction temperature for the CPOM process, the selectivity for H-2 was affected to a much lesser extent. The selectivity for CO and H-2 in the CPOM reaction was found to decrease with increasing space velocity; the H-2 selectivity was however affected to a greater extent. For the OSRM process, the H2O/CH4 ratio profoundly influenced the H-2/CO ratio and the heat of the reaction. Depending on the H2O/CH4 ratio, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion increased rapidly with increasing OCRM temperature and correspondingly the exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. At 900 degrees C, the OCRM reaction was mildly exothermic and provided high methane conversion and syngas selectivity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: high temperature stable catalyst; methane; oxy-dry reforming; oxy-steam reforming; Partial oxidation